Analisis Bahasa Ken dalam Reality Show Dairy Sarwendah - Indah Wahyuningsih; Meita Ardya Fahma; Muhammad Rais Almajid (Institut Agama Islam Negeri Curup, 2020)
This study aimed to describe Ken language in a reality show